COMT Val158Met Polymorphism Exerts Sex-Dependent Effects on fMRI Measures of Brain Function - Elton, Amanda; Smith, Christopher T.; Parrish, Michael H.; Boettiger, Charlotte A. (Frontiers in Human Neuroscience, 2017)
Evidence suggests that dopamine levels in the prefrontal cortex (PFC) modulate executive functions. A key regulator of PFC dopamine is catechol-O-methyltransferase (COMT). The activity level of the COMT enzyme are influenced by sex and the Val158Met polymorphism (rs4680) of the COMT gene, with male sex and Val alleles both being associated with higher bulk enzyme activity, and presumably lower PFC dopamine. COMT genotype has not only been associated with individual differences in frontal dopamine-mediated behaviors, but also with variations in neuroimaging measures of brain activity and functional connectivity. In this study, we investigated whether COMT genotype predicts individual differences in neural activity and connectivity, and whether such effects are sex-dependent. We tested 93 healthy adults (48 females), genotyped for the Val158Met polymorphism, in a delay discounting task and at rest during fMRI. Delay discounting behavior was predicted by an interaction of COMT genotype and sex, consistent with a U-shaped relationship with enzyme activity. COMT genotype and sex similarly exhibited U-shaped relationships with individual differences in neural activation, particularly among networks that were most engaged by the task, including the default-mode network. Effects of COMT genotype and sex on functional connectivity during rest were also U-shaped. In contrast, flexible reorganization of network connections across task conditions varied linearly with COMT among both sexes. These data provide insight into the potential influences of COMT-regulated variations in catecholamine levels on brain function, which may represent endophenotypes for disorders of impulsivity.